Complicating the rhetoric: How racial construction confounds market-based reformers' civil rights invocations - Laura Elena Hernandez (Arizona State University, 2016)
Reformers today maintain the use of civil rights rhetoric when advocating for policies that address educational inequity. While continuing the legacy of earlier civil rights activists, the leaders invoking this rhetoric and the educational platforms they promote differ greatly from previous decades. Not only does this new crop of reformers differ demographically, they also tend to promote market-oriented initiatives like the expansion of charter schools and other school choice initiatives, which embody market logics alongside a sharp retrenchment from the public sphere. While scholars have revealed how these policies generate questionable outcomes for students and communities of color, few have considered the manner in which marginalized racial groups are characterized and framed amidst these reforms and cries for civil rights. In this empirical paper, I use Critical Discourse Analysis (CDA) to analyze how race-based constructions complicate the use of civil rights rhetoric in today's increasingly marketized educational context. Specifically, I investigate how two educational leaders discuss race within comments about education and its connection to civil rights. The findings suggest that the leaders allude to race without explicitly naming it in the context of civil rights discourse. In addition, their civil rights invocations exist alongside subtly constructed, negative racial narratives that they articulate in the context of their statements. Given these findings, this paper ends with a discussion of these seemingly incompatible discourses. In particular, I interrogate how these racial constructions reflect the characteristics of colorblindness and how this, in turn, may undermine policies the aim to address racial inequity.